Assessment of overweight and obesity among urban adolescents - Chaudhary, Ansh; Pokale, Aarati; Narula, A. P. S.; Chaudhary, Bhupendra; Misra, Ankita; Jain, Ayush (International Journal of Contemporary Pediatrics, 2019)
Background: Obesity is defined as the abnormal growth of adipose tissue due to enlargement of fat cell size or increase in their number or a combination of both. Adolescents are nutritionally vulnerable age group considering their increased nutritional needs, eating patterns, lifestyle and susceptibility to environmental influences. The present study was conducted with aims to access the prevalence of overweight and obesity among urban adolescents and to study various factors associated with overweight and obesity. Methods: A community based cross sectional study of 872 adolescents of both sexes in urban population of Pune, Maharashtra, India was conducted to assess prevalence and various factors influencing overweight and obesity, especially type of diet, frequency of junk foods, physical activity and sleeping habits. The Body Mass Index (BMI) and Waist-Hip Ratio (WHR) were used to define overweight and obesity as per WHO growth standards. Results: The prevalence of overweight and obesity in urban adolescents according to BMI were 17.4% and 6.9% respectively with overall prevalence being 24.3% but with Waist-Hip Ratio (WHR) it was 43.1%. Risk factors in urban areas were consumption of fast/junk food, carbonated drink, physical inactivity while afternoon sleep was not a significant factor. Conclusions: This study showed an increased prevalence of overweight and obesity in urban adolescents especially in those who have more consumption of fast food, carbonated drink, those who were either inactive or engaged in physical activity for less than 30 min/day were strongly associated with overweight and obesity.